Evaluation of Physicochemical parameters of samples from irrigated farms at Hweng, Foron District, Plateau State, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The research work focused on the evaluation of Physicochemical parameters in samples from irrigated farms at Hweng, Foron District, Plateau State, Nigeria. The water, soil and plant samples were collected from the irrigated farms, Different analytical methods were used to determine the concentrations. The Physicochemical parameters analyzed were electrical conductivity (EC), turbidity, total dissolved solid. (TDS), total hardness, dissolve oxygen (DO), biochemical oxygen demand (BOD), alkalinity, oil and grease (O/G), chemical oxygen demand (COD), nitrate, nitrite, sulphate and chloride. pH ranged from 6.5-69, EC ranged from 122-139 uS/cm, turbidity ranged from 0.83-205 NTU, TDS ranged from 80-90, hardness ranged from 27-48 mg/dm³, alkalinity ranged from 7-44g dm³, DO ranged from 6.8-8.4 mg dm³, BOD ranged from 1.11-3.4 mg dm³,, O/G ranged from 0-0.2 mg dm³, COD ranged from 1.6-48 mg dm³, nitrate ranged from 0.3-13 mg dm³, nitrite ranged from 0.2-0.4 mg dm³, sulphate ranged from 4.9-48.3 mg dm³, chloride from 0-0.1 mg dm³. Pearson correlation was used and all the parameters had a position relationship with each other. Water samples of rainy and dry seasons, and water samples of dry and control were not statistically significant while the rest had a statistically significant values.